Quality Assessment of Used Palm Cooking Oil Processed by Microfiltration Using Whatman Filter Papers with Different Pore Sizes - Poppy Diana Sari; Rukmi Sari Hartati; Syamsudduha Syahrorini; I Nyoman Setiawan; Rahmah Utami Budiandari; I Wayan Sukerayasa; Muhammad Ainnur Rafdiansyah (Green Engineering Society, 2026)
Microfiltration is a preliminary treatment in the production of biodiesel. This method is characterized by its simplicity and its environmental friendliness. It can reduce foam production during the saponification process, which is generally concomitant with the esterification process. Furthermore, microfiltration process does not involve the use of chemicals. The micropore size of the filter greatly influences the quality of the biodiesel produced, given its impact on impurities present in the oil used. The present study sought to determine the effect of microporous membrane size on the quality of used frying oil. The treatment variables in this study were the micropore sizes of the Whatman filter paper used: 2.5 μm, 8 μm, 11 μm, 16 μm, 20 μm, and 25 μm. Meanwhile, the observation variables encompassed the free fatty acid (FFA) content, acid number, viscosity, and water content of the used cooking oil. The findings of the study indicate that the microfiltration treatment employing filter paper with 2.5 μm pore size yielded the best results, with free fatty acid (FFA) level, acid number, viscosity and water content of 0.00238%, 0.411 mg KOH/g, 3.2843 cSt and 0.00068%, respectively. In accordance with the stipulations outlined in the Indonesian National Standard (SNI) 7128:2015, the microfiltered oil obtained in this study is deemed suitable for use as a raw material in biodiesel production.